A New Methodological Approach to Study the Interaction of Humic Acids, Minerals and Polyvalent Cations in Soil - Kloster, Nanci Soledad; Puccia, Virginia; Fernandez, Romina; Avena, Marcelo; Tan, Wenfeng; Wang, Mingxia (Taylor & Francis, 2024)
A new methodological approach of humic acid (HA) extraction is applied to study soil samples with contrasting management regimes: natural vegetation (NV) and agricultural (A). This innovative approach involves a modification of the Swift’s method, wherein several steps HCl/HF are replaced by a single-step HCl/HF. This modification enabled us to investigate the ability of HA to retain inorganic constituents. The carbon content was significantly higher in soils under NV (19.8–27.3 g C kg−1) than under A (11.2– 13.4 g C kg−1). The same pattern was observed for the HA content. The new methodology revealed that HA from NV soils had a much higher capacity to retain inorganics (ash contents in HA from 12.3–28.3%) than in A soils (ashcontent in HA from 1.6–2.6%). Similar results were found for Ca+Al+Fe contents in the HA (3.7–2.5 meq g−1 in HA from NV soils; 2.2–.9 meq g−1 in HA from A soils). Some differences were observed in IR spectra, mainly an intense band at around 1050 cm−1 of HA from NV that reflects the high ash content of the HA and its capacity of retaining inorganic material. Ca binding isotherms of HA also showed that the HA differed significantly in their ability to retain inorganic components when extracted. Humic acid from NV was more efficient in retaining metal ions and minerals than HA from A soils. All results point to a better contact between organic and inorganic matter in NV soils, and this contact contributes to the stabilization of organic matter.